Research on multi-group dual piezoelectric energy harvester driven by inertial wheel with magnet coupling and plucking. (1st September 2021) - He, Lipeng; Zhou, Jianwen; Zhang, Zheng; Gu, Xiangfeng; Yu, Yaling; Cheng, Guangming
Highlights: Using multiple groups of magnet coupling and plucking harvesters driven by inertial wheel. In contrast to previous study, we have made a parametric study of the piezoelectric energy harvester structure. It can generate milliwatt-level electrical energy at a smaller resonance frequency. Abstract: Piezoelectric technology has attracted extensive attention and played an increasingly important role in the aspect of harvesting energy from the environment, which has advantages of simple structure, good performance, and so on. In this study, a multi-group dual piezoelectric energy harvester driven by inertial wheel with magnet coupling and plucking (M−PEH) is proposed. The M−PEH mainly includes a base, supports, piezoelectric patches, magnets, magnets cover, and rotor. This paper studies the series–parallel connection relationship between the circular and rectangular piezoelectric patches in the circumferential direction of the base, and the influence on the peak-to peak voltage when the length of the magnet extending from the surface of the rotor is different. Under the condition of inertial wheel 407 g, the M−PEH is tested and researched from 50 r/min to 600 r/min. After a series of experimental studies at 550 r/min, the peak-to-peak voltages of the circular and rectangular piezoelectric patches are respectively 15.00 V, 28.74 V, and 34.37 V, 67.19 V in the case of parallel and series connection when the length of the magnet protruding from the surface of the rotator is 7 mm. Besides that, under the condition of series connection, it is shown that the root-mean-square voltage and power of the circular and rectangular piezoelectric patches are 3.37 V, 0.054 mW, and 10.03 V, 0.80 mW, respectively at 550 r/min when the resistance is 100 kΩ. It can also easily light 47 light-emitting diodes (LEDs) under the excitation of 550 r/min. Therefore, the M−PEH can effectively collect energy under the drive of the inertia wheel and power the microelectronic devices.